Pengaruh Keterlibatan Kerja dan Budaya Kerja Terhadap Produktivitas Kerja Pegawai di Kantor Gubernur Provinsi Kalimantan Timur (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of work engagement and organizational culture on employee productivity at the Bureau of Leadership Administration, Governor's Office of East Kalimantan Province. Work engagement involves employees’ active participation, emotional commitment, and sense of belonging toward their roles and organization. Organizational culture includes values, norms, and behaviors that shape the workplace environment. A quantitative approach was used with a questionnaire distributed to 69 employees. The results of multiple linear regression analysis show that work engagement has a positive and significant impact on productivity, with a significance value of 0.002 and regression coefficient of 0.589. Organizational culture also shows a significant effect with a significance value of 0.000 and coefficient of 0.527. Simultaneously, both variables significantly influence productivity, as indicated by an F-value of 37.655 and an R² of 0.533. This means that 53.3% of the variation in productivity is explained by the two variables. The findings highlight the importance of fostering a supportive and value-driven work environment as a key strategy to improve employee productivity.